Sequência de ensino investigativo sobre sexualidade construída a partir das contribuições de estudantes do ensino médio e professores de ciências/biologia - Agostini, Jeane Pignaton (2022)
Sexuality is a relevant topic, as it is related to human life and health. Despite its importance, the subject is still not discussed in many schools, even though it is a cross-cutting topic. That said, it was proposed to elaborate a sequence of investigative teaching on sexuality from the contribution of high school students and science/biology teachers. To this end, the objective was to identify which are the dialogues produced by high school students and biology/science teachers when it is possible to discuss this theme. Thus, the students' doubts were collected through the doubts box and/or online questionnaire and then science/biology teachers answered an online questionnaire about their training and teaching practice with this theme, and also participated in a focal group. These data were used to develop a sequence of investigative teaching on sexuality to overcome myths and acquire scientific knowledge. After completion, the sequence was sent to the participating teachers for analysis, evaluation and suggestions through an online questionnaire and later, it was applied to high school students, who, in the end, completed an evaluation questionnaire. As it is an action research, data were also collected through participant observation of the researcher. Despite the challenges of prejudice, student maturity, religion, taboo and lack of training, teachers suggest strategies to teach on the subject, such as a question box, conversation circle, debates, reporting and have shown interest in using the sequence in their classes. The teaching sequence was organized into four sub-themes: I) respect for the body, pleasure, gender identity and sexual orientation; II) anatomy of the female and male reproductive system; III) menstrual cycle, pregnancy, childbirth and abortion; IV) STIs and contraceptive methods. This sequence has 15 classes with diversified activities, such as: representation of the menstrual cycle with PET bottle caps, simulated jury and practical class simulating fluid exchanges. During the realization of this sequence, the interest and engagement of students was observed. The sequence also met the objective of solving the students' difficulties, expanding knowledge about the concept of sexuality, the differences between gender identity and sexual orientation, knowing other STIs, contraceptive methods and the psychological, social and financial implications of pregnancy in adolescence, in addition to discussions with arguments about abortion. In this way, it overcame students' myths about sexuality and added scientific knowledge on the subject.